DNA ADP-Ribosylation Stalls Replication and Is Reversed by RecF-Mediated Homologous Recombination and Nucleotide Excision Repair - Lawarée, Emeline (Cell Rep, 2019)
ADP-ribosylation of proteins is crucial for fundamental cellular processes. Despite increasing examples of DNA ADP-ribosylation, the impact of this modification on DNA metabolism and cell physiology is unknown. Here, we show that the DarTG toxin-antitoxin system from enteropathogenic Escherichia coli (EPEC) catalyzes reversible ADP-ribosylation of single-stranded DNA (ssDNA). The DarT toxin recognizes specific sequence motifs. EPEC DarG abrogates DarT toxicity by two distinct mechanisms: removal of DNA ADP-ribose (ADPr) groups and DarT sequestration. Furthermore, we investigate how cells recognize and deal with DNA ADP-ribosylation. We demonstrate that DNA ADPr stalls replication and is perceived as DNA damage. Removal of ADPr from DNA requires the sequential activity of two DNA repair pathways, with RecF-mediated homologous recombination likely to transfer ADP-ribosylation from single- to double-stranded DNA (dsDNA) and subsequent nucleotide excision repair eliminating the lesion. Our work demonstrates that these DNA repair pathways prevent the genotoxic effects of DNA ADP-ribosylation.